OBTAINING AN ACID-BASE NATURAL INDICATOR FROM THE FRUIT Punica granatum l. (POMEGRANATE): A CONTRIBUTION FOR THE SUBSTITUTION OF SYNTHETIC INDICATORS. - Huarote, Emily Guissel; Herrera, Nora Gabriela; Borquez, Jorge (Journal of the Chilean Chemical Society, 2019)
The research proposes to obtain a natural acid-base indicator from the extract of the arils of the Punica granatum L.(pomegranate) fruit as an option to replace the synthetic indicators (phenolphthalein). The indicative actions of the fruit extract Punica granatum L. is due to the presence of phytochemicals (anthocyanins). The identification of some of the anthocyanins present was carried out by an analysis in the UHPLC-ESI-Q-Orbitrap-MS / MS equipment, of Reverse Phase C-18. The preliminary tests for the anthocyanin test were to measure the color change of the extract against HCl and NaOH, likewise a pH scale curve was performed and its stability was measured in different periods of time (5, 10 and 15 min), which were analyzed in the UV-Vis Spectrophotometer, the potentiometric acid-base titrations, determined the values ​​of the first and second derivatives, obtaining the pKInd interval of the fruit extract Punica granatum L. Finally, it was confirmed that the pH variation is one of the factors that significantly affected the color of the extract of the Punica granatum L. fruit, while the effect of light at different time periods oxidized the extract (discoloration).